Molecular recognition of B-DNA by Hoechst 33258. - Harshman, K D (1985)
The binding sites of Hoechst 33258, netropsin and distamycin on three DNA restriction fragments from plasmid pBR322 were compared by footprinting with methidiumpropyl-EDTA X Fe(II) [MPE X Fe(II)]. Hoechst, netropsin and distamycin share common binding sites that are five +/- one bp in size and rich in A X T DNA base pairs. The five base pair protection patterns for Hoechst may result from a central three base pair recognition site bound by two bisbenzimidazole NHs forming a bridge on the floor of the minor groove between adjacent adenine N3 and thymine O2 atoms on opposite helix strands. Hydrophobic interaction of the flanking phenol and N-methylpiperazine rings would afford a steric blockade of one additional base pair on each side.